Estrategias de marketing en el comercial Burbano de la ciudad de Babahoyo, periodo 2022. - Mestanza Zambrano, Byron Octavio (2023)
The objective of this case study is to analyze the marketing strategies of Comercial Burbano using research techniques to determine the position of the business in the market. At the same time, identify the techniques that are currently used by interviewing the owner to find flaws in the procedures, evaluate the service through customer surveys to know their criteria and, based on the research, provide suggestions that will boost business sales. The investigation shows that the salesperson has focused on using marketing and direct sales techniques, that is, only those that are carried out with the personal interaction of the seller and the client, he does not have an online presence, limiting exposure and interaction with current and potential clients with the products and services of the business. Among the recommendations are executing loyalty strategies such as good service, offering discounts and promotions that encourage purchases; implement various forms of payment, cumulative plan, credit cards that make it easier to carry out transactions with the business; Add digital communication systems for adequate customer service and maintain an adequate image of the commercial premises.